Technology Acceptance Model (TAM) of Magic Book Augmented Reality by Hippo as a Reading Medium for Junior High School Students in Padang: A Study of Students’ Perception - Wiji Kholifah; Nora Fudhla (Universitas Negeri Padang, 2023)
The language learning process in today's modern era certainly requires technology-based learning media that supports learning. Magic Book Augmented Reality by Hippo is a technology that can be used to support the English learning process. The purpose of this study was to learn about students' perceptions of the use of Magic Book Augmented Reality by Hippo based on the Technology Acceptance Model (TAM), using two indicators; Perceived Ease of Use (PEOU) and Perceived Usefulness (PU). The population of this study was students in the ninth grade at SMP Negeri 20 Padang during the academic year 2023/2024. This study used convenience sampling with a total sample of 30 students. This study was conducted as a descriptive study, and the data were analyzed using a quantitative methodology. Based on the data collected using the questionnaire as an instrument, it is possible to conclude that using Magic Book Augmented Reality by Hippo as a reading medium for learning English based on the Technology Acceptance Model (TAM) resulted in very positive perceptions by the students. Students also had very positive perceptions of the ease of use and usefulness of Magic Book Augmented Reality by Hippo in the context of learning English narrative text.